Mammillaria monochrysacantha (Cactaceae), a new endemic species from Guanajuato, Mexico - González-Zamora, Pedro; Aquino, David; Rodríguez, Aarón; Sánchez, Daniel (Phytotaxa, 2023)
A new species of Mammillaria ser. Stylothelae is described and illustrated. Mammillaria monochrysacantha is distinguished from other species of the series by having a globose stem with fibrous roots, one single golden yellow hooked central spine, 28–32 tortuous hair-like radial spines, flowers with lanceolate pale yellow tepals, and non-arilloid seeds. We provided a comparison with other morphologically close and sympatric species of Mammillaria. The new species is endemic from the Sierra Gorda, Guanajuato, Mexico. We included data about its habitat and the status of conservation. Additionally, we integrated an identification key for M. ser. Stylothelae from Guanajuato, San Luis Potosí, and Querétaro, Mexico.